Diploid construction by protoplast fusion in Fulvia fulva (syn. Cladosporium fulvum): genetic analysis of an imperfect fungal plant pathogen - Talbot, N.; Coddington, A.; Roberts, I.; Oliver, Richard (1988)
Auxotrophic and drug resistant mutants have been isolated in five of the seven races of Fulvia fulva (syn. Cladosporium fulvum) following UV mutagenesis. Drug resistant mutants have also been isolated by genetic transformation using vectors conferring resistance to hygromycin B and phleomycin. Protoplasts of complementing auxotrophs or mutants with different drug resistances have been fused to form diploids as demonstrated by growth characteristics and microfluorimetry. Some of the diploid fusion products remained stable but most went on to haploidise spontaneously. Using this technique it is now possible to perform both complementation and linkage analysis in an imperfect fungal plant pathogen.